APPLICATION OF BUILDING INFORMATION MODELING 3D, 4D, AND 5D IN THE DESIGN PLANNING OF IHM DOCK ACCESS ROAD - Wardani, Muhammad; Waluyo, Rudi; Purwantoro, Almuntofa (Jurnal Disprotek, 2025)
Along with the times, infrastructure development is increasingly complex, especially in terms of road planning. An innovation is needed to face these challenges. Before the introduction of the building information modeling (BIM) method, road planning still used conventional methods. Many studies have revealed that the BIM method is more accurate and superior compared to conventional methods. The PT ITCI Hutani Manunggal (IHM) jetty access road construction package still uses conventional methods in its planning. So the plan for the road construction project was updated by applying BIM technology. The objective of research are  to know implementation of 3D, 4D, and 5D BIM on integration of road redesign. This research was conducted for two months with the location in Penajam Paser Utara Regency. The data analysis technique using the BIM Method consists of 3 stages, namely modeling alignment and profile plans, integration of total costs into the BIM model, integration of work duration into the BIM model. The results of the application of 3D BIM provide a clear initial picture of the shape of the infrastructure to be built, and the application of 4D BIM provides a detailed visualization of construction progress with a 270-day scheduling plan, and the application of 5D BIM describes the cost aspects in an integrated manner with the total planning cost obtained of Rp 166,491,010,588. With the integration of these three dimensions in the BIM model, cost, schedule, and quality estimation becomes more organized and transparent.PENERAPAN BUILDING INFORMATION MODELLING 3D, 4D, DAN 5D PADA PERENCANAAN DESAIN JALAN AKSES DERMAGA IHMSeiring dengan perkembangan zaman pembangunan infrastruktur semakin kompleks, terutama dalam hal perencanaan jalan. Perlu sebuah inovasi dalam menghadapi tantangan tersebut. Sebelum dikenalnya metode building information modeling (BIM), perencanaan jalan masih banyak menggunakan metode konvensional. Banyak penelitian yang mengungkapkan bahwa metode BIM lebih akurat dan unggul dibandingkan dengan metode konvensional. Paket pembangunan jalan akses Dermaga PT. ITCI Hutani Manunggal (IHM) masih menggunakan metode konvensional dalam perencanaannya. Maka rencana untuk proyek konstruksi jalan tersebut diperbarui dengan menerapkan teknologi BIM. Penelitian ini bertujuan untuk mengetahui penerapan BIM 3D, 4D, dan 5D pada redesain jalan yang saling terintegrasi. Penelitian ini dilakukan selama dua bulan dengan lokasi di Kabupaten Penajam Paser Utara. Teknik analisis data menggunakan Metode BIM terdiri dari 3 tahapan yaitu permodelan alignment dan profile rencana, integrasi total biaya terhadap model BIM, integrasi durasi pekerjaan terhadap model BIM. Hasil penelitian menunjukkan bahwa penerapan BIM 3D memberikan gambaran awal yang jelas terhadap bentuk infrastruktur yang akan terbangun, penerapan BIM 4D memberikan visualisasi progres konstruksi secara detail dengan rencana penjadwalan selama 270 hari, serta penerapan BIM 5D menggambarkan aspek biaya secara terintegrasi dengan total biaya perencanaan diperoleh sebesar Rp 166.491.010.588. Dengan integrasi ketiga dimensi tersebut dalam model BIM, estimasi biaya, jadwal, dan mutu menjadi lebih terorganisasi dan transparan.